How do gender values and household practices cohere? Value-practice configurations in a gender egalitarian context - Randi Kjeldstad; Trude Lappegård (Statistics Norway, Research Department, 2012)
Previous research shows a paradoxical simultaneity of egalitarian gender values and inegalitarian practices in Europe. The Socio-democratic welfare states stand out with the most coherent egalitarian value-practice configurations. With this as a point of departure we examine the coherencies and incoherencies between gender values and household practices in Norway, a socio-democratic and prevailing gender egalitarian country. Based on data from the Norwegian Generations and Gender survey, we estimate four distinct types of value-practices in families, using a multinomial logit latent class regression technique. The analysis reveals a relatively high proportion of couples reporting coherent gender egalitarian values and practices. But we also find quite frequently reported incoherent configurations. These are significantly gendered, and what is often denoted as a paradoxical simultaneity of egalitarian values and inegalitarian practices proves to be mainly a female paradox. At the same time, our study has unveiled an equally frequent incoherency of inegalitarian values and egalitarian practices, reflecting mainly a male paradox. The gendered "paradox" of incoherencies between values and practices is assumed to be attributed largely to women's and men's dissimilar perception of how the everyday household work is actually apportioned between the partners.
Keywords: J22; 330; Gender values; division of housework and childcare; value-practice configurations; gender perception